Sex differences evident in elevated anxiety symptoms in multiple sclerosis, inflammatory bowel disease, and rheumatoid arthritis - Joyees, Jerlin; Marrie, Ruth Ann; Bernstein, Charles N.; Bolton, James M.; Fisk, John D.; Graff, Lesley A.; Hitchon, Carol; Patten, Scott B.; Kowalec, Kaarina; , for the CIHR team in defining the burden; managing the effects of psychiatric comorbidity in chronic immunoinflammatory disease; Marrie, Ruth Ann; et al. (Frontiers in Psychiatry, 2023)
Introduction: Immune-mediated inflammatory diseases (IMID), such as multiple sclerosis (MS), inflammatory bowel disease (IBD) or rheumatoid arthritis (RA) have high rates of elevated anxiety symptoms. This can may worsen functioning and increase IMID disease burden. The rate of and factors associated with elevated anxiety symptoms may differ between males and females, which, in turn can affect diagnosis and disease management. We evaluated whether the frequency and factors associated with comorbid elevated anxiety symptoms in those with an IMID differed by sex. Methods: Participants with an IMID (MS, IBD or RA) completed two anxiety measures (HADS, GAD-7). We used logistic regression to investigate whether sex differences exist in the presence of comorbid elevated anxiety symptoms or in the endorsement of individual anxiety items in those with an IMID. Results: Of 656 participants, females with an IMID were more likely to have elevated anxiety symptoms compared to males (adjusted odds ratio [aOR] 2.05; 95%CI: 1.2, 3.6). Younger age, higher depressive symptoms and income were also associated with elevated anxiety symptoms in IMID. Lower income in males with an IMID, but not females, was associated with elevated anxiety symptoms (aOR: 4.8; 95%CI: 1.5, 15.6). No other factors demonstrated a sex difference. Males had nearly twice the odds of endorsing restlessness on the GAD-7 (OR=1.8, 95%CI: 1.07, 3.15) compared to females. Discussion: We found evidence for sex differences in the factors associated with experiencing elevated anxiety symptoms in those with an IMID. These findings could be helpful to sensitize clinicians to monitor for comorbid anxiety symptoms in males with an IMID.